Dynamic Analysis Of The Local Government Revenue Generation Of Padang City Before And After The Regional Autonomy - Aryadi, Didi; Handra, Hefrizal; Elfindri, Elfindri; Ridwan, Endrizal (Opción, 2019)
This research focused on the DAU, investment and population growth factors towards regional revenue consisting of Regional Tax and Non Tax Revenue Posts. The analysis also focused on the analysis of the presence or absence of the flypaper effect on the realization of the Padang City Government’s APBD before and after regional autonomy. This research is classified as descriptive and associative research and also expo facto. The data of all variables in this study were collected from 1980 to 2018 in the city of Padang. This study used regression analysis, that is, .... The analysis shows that 1) DAU has a signifi- cant effect on Padang City Tax PAD 2) Investment has no significant effect on Padang City Tax PAD 3) Regional autonomy policy has a significant effect on Padang City Tax PAD 4) Population Growth has no significant effect on Pa- dang City Tax PAD 5 ) DAU has a significant effect on Padang City’s Non-Tax PAD 6) Investment has no significant effect on Padang City’s Non-Tax PAD 7) Regional autonomy policy has no significant effect on Padang City’s Non-Tax PAD 8) Population growth has a significant effect on Padang City’s Non-Tax PAD 9) Tax PAD has a significant effect on Regional Spending in Padang City 10) Non-Tax PAD has a significant effect on Regional Spending in Padang City 11) No flypaper effect occurs on regional expenditure of the realization of the Padang City Regional Budget.